Clinical Application of Cone-Beam CT (CBCT) in the Delivery of Hypofractionated Radiotherapy for Muscle-Invasive Bladder Cancer (MIBC): Ensuring Adequate Planning Target Volume Coverage and Small Bowel Sparing - Riaz, Omer; Mahmood, Ahsan; Wajid, Imran; Maqsood, Talha; Khan, Muhammad Uzair (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate the clinical application of cone-beam CT (CBCT)-guided image-guided radiotherapy (IGRT) in muscle-invasive bladder cancer (MIBC), assessing planning target volume (PTV) coverage at the 95% isodose line, dose to the small bowel, and the feasibility of PTV margin reduction. Study Design: Prospective observational study. Place and Duration of Study: Department of Radiation Oncology, Combined Military Hospital/NUMS, Rawalpindi Pakistan, from Nov 2025 to Mar 2026. Methodology: Thirty-one patients with histopathologically proven muscle-invasive urothelial carcinoma (stage T2–T4, N0–N1, M0) were enrolled following Ethical Review Committee approval. CT simulation was performed with an empty bladder. A dose of 55 Gy in 20 fractions was delivered by VMAT (Eclipse TPS v16.1; Varian CLINAC DHX 2300 / VitalBeam) with a 1.5 cm PTV margin, and daily CBCT enabled online soft-tissue verification and correction. Concurrent weekly cisplatin 40 mg/m² was given where clinically appropriate. Data were analysed using IBM SPSS Statistics version 26. Results: All 31 patients completed treatment. Mean age was 69.6±10.5 years; 17(54.8%) had T2 disease and 23(74.2%) were node-negative. Adequate PTV coverage at the 95% isodose line (≥95%) was achieved in all 31(100%) patients, with a mean coverage of 97.5±1.1%. The mean dose to 98 cc of small bowel was 30.94±15.44 Gy, within the accepted constraint. PTV margin reduction from 1.5 cm to 1.0 cm was considered feasible in 19(61.3%) patients. Conclusion: CBCT-guided IGRT using VMAT achieved excellent target coverage with acceptable small bowel doses in MIBC, and supported PTV margin reduction in a majority of patients.